Individualized Whole-Body Vibration: Neuromuscular, Biochemical, Muscle Damage and Inflammatory Acute Responses - Riccardo Di Giminiani; Nadia Rucci; Lorenzo Capuano; Marco Ponzetti; Federica Aielli; Jozsef Tihanyi (SAGE Publishing, 2020)
Objective . We aimed to investigate the acute residual hormonal, biochemical, and neuromuscular responses to a single session of individualized whole-body vibration (WBV) while maintaining a half-squat position. Methods. Twenty male sport science students voluntarily participated in the present study and were randomly assigned to an individualized WBV group (with the acceleration load determined for each participant) or an isometric group (ISOM). A double-blind, controlled parallel study design with repeated measures was employed. Results. Testosterone and growth hormone increased significantly over time in the WBV group ( P < .05 and P < .01, respectively; effect size [ES] ranged from 1.00 to 1.23), whereas cortisol increased over time in both groups ( P < .01; ES ranged from 1.04 and 1.36). Interleukin-6 and creatine kinase increased significantly over time only in the WBV group ( P < .05; ES = 1.07). The maximal voluntary contraction decreased significantly over time in the ISOM group ( P = .019; ES = 0.42), whereas in the WBV group, the decrease did not reach a significant level ( P = .05). The ratio of electromyographic activity and power decreased significantly over time in the WBV group ( P < .01; ES ranged from 0.57 to 0.72). Conclusion. Individualized WBV increased serum hormonal concentrations, muscle damage, and inflammation to levels similar to those induced by resistance training and hypertrophy exercises.